Visual outcome of congenital and developmental cataract surgery in Lumbini Eye Institute - Hirachan, Anjita; Bajracharya, Kabindra; KC Rai, Salma; Malla Bhari, Arjun; Chandra, Avinash (Asian Journal of Medical Sciences, 2018)
Background: Paediatric blindness presents as an enormous problem to developing countries in terms of human morbidity, economic loss and social burden. Aims and Objective: The objective of this study was to observe the visual outcome of congenital and developmental cataract surgery. Materials and Methods: This study was prospective, longitudinal and interventional. The patients aged ≤15 years, diagnosed either congenital or developmental cataract and planned for cataract surgery were enrolled during March 2014 to February 2015 at Lumbini Eye Institute, Nepal. The patients underwent either: a) Lens aspiration + PPC+ Anterior Vitrectomy; b) Lens aspiration + PPC+ Anterior Vitrectomy + PCIOL; c) Lens Aspiration + PCIOL depending upon age of patient. The patients were examined after surgery day 1, day 2, after 2 weeks and after 6 weeks. Glasses were prescribed at 6 weeks from the date of surgery. Occlusion therapy was initiated in cases wherever necessary. Results: A total of 54 eyes of 43 children were included in the study. The sex ratio was 1.26 female per male with mean age of 3 years (SD ± 2.16). In the verbal group, 61.1% (33 eyes) had final visual acuity (6/6-6/18). In the non verbal group, 16.7% (9 eyes) had final visual acuity of good fixation and follow. There was a statistically highly significant improvement in post surgical Best corrected visual acuity (p< 0.001). Conclusion: Good visual outcome after pediatric cataract surgery can be obtained if surgery is performed by skilled surgeon. The awareness of pediatric cataract, early diagnosis and timely intervention to surgical treatment, and postoperative management of residual uncorrected refractive error and amblyopia are important factors for the prevention of childhood blindness from cataract. Asian Journal of Medical Sciences Vol.9(2) 2018 36-39